Participation in international un iversity rankings as a factor of improving the quality of teaching and learning - Sergey V. Ablameyko; Michail A. Gusakovsky (Высшее образование в России)
The role and practical significance of international university rankings are discussed asmeans of improving the quality of teaching and learning, research and management. Special focus is made on Belarusian State University’ participation in the international rankings QS WUR, Webometrics, SCImago Institutions Rankings (SIR), University Ranking by Academic Performance (URAР).